2014
DOI: 10.4155/fmc.13.190
|View full text |Cite
|
Sign up to set email alerts
|

Proposing Advancement Criteria for Efficient Dmpk Triage of New Chemical Entities

Abstract: With the goal of refining our discovery DMPK workflow, we conducted a retrospective analysis on internal Celgene compounds by calculating the physicochemical properties and gathering data from several assays including solubility, rat and human liver S9 stability, Caco-2 permeability, and rat intravenous (iv.) and oral pharmacokinetics. Our analysis identified plasma clearance to be most statistically relevant for prediction of oral exposure. In rat, compounds with rat S9 stability of ≥70% at 60 min and a plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Poor permeability would potentially lead to higher apparent rates of stability in hepatocytes, owing to their inability to enter the hepatocytes to be exposed to the metabolic enzymes. Indeed, we found that 75% of compounds that fell into this category and had Caco-2 data, exhibited poor permeability according to the permeability criteria that we have published previously [8] (P app < 8 X 10 -6 cm/s). Excluding such compounds from the analysis, the discrepancy between S9 and hepatocyte acceptance rate dropped to 13% in the rat (from 20%) and 7% in the human S9 (from 11%).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Poor permeability would potentially lead to higher apparent rates of stability in hepatocytes, owing to their inability to enter the hepatocytes to be exposed to the metabolic enzymes. Indeed, we found that 75% of compounds that fell into this category and had Caco-2 data, exhibited poor permeability according to the permeability criteria that we have published previously [8] (P app < 8 X 10 -6 cm/s). Excluding such compounds from the analysis, the discrepancy between S9 and hepatocyte acceptance rate dropped to 13% in the rat (from 20%) and 7% in the human S9 (from 11%).…”
Section: Resultsmentioning
confidence: 52%
“…In doing so, we used the “70% remaining at 60 minutes” criteria post-incubation as listed in our prior publication [8]. Compounds with ≥ 70% parent remaining at 60 minutes were labeled as “pass” and the remaining were labeled as “fail”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human hepatocytes are considered to be golden standard and 7-ethoxy coumarin has been used as an appropriate substrate to understand the phase-I and phase-II metabolism [31] in different matrices. Recently liver S9 fractions were shown as a matrix comparable to that of hepatocytes to screen compounds for metabolic stability assays [32]. Researchers have used 7-ethoxy coumarin and performed a comparative study on three different matrices i.e.…”
Section: In Vitro Metabolism Of Drugs By Liver S9 Fractionsmentioning
confidence: 99%